The effect of foot reflexology on the volume and composition of breast milk in mothers of premature infants hospitalized in the neonatal intensive care unit: a randomized controlled trial - Fateme Norouzi Nodehi; Parvin Aziznejadroshan; Hossein-Ali Nikbakht; Mohsen Haqshanas; Sohrab Halakhor (BMC Pediatrics, 2024)
Abstract Background One of the important problems for mothers after the birth of a premature infant is a decrease in milk production. This study aimed to investigate the effect of foot reflexology on the volume and composition of breast milk in mothers of premature infants hospitalized in the neonatal intensive care unit. Methods This randomized clinical trial was conducted on 76 primiparous mothers whose premature infants up to 34 weeks were hospitalized in the neonatal intensive care unit of Ayatollah Rouhani Hospital from February 2023 to November 2023. Mothers in the intervention group received foot reflexology for 20 min on both feet (ten minutes per foot) for seven consecutive days every morning. On the first and seventh days of the study, both groups were compared in terms of milk volume (ml), triglycerides, cholesterol, albumin, total protein, and calcium (mg/dl). Results The mean difference in breast milk characteristics before and after the intervention in the control and intervention groups were as follows: in terms of breast milk volume 12.43 and 23.51 ml, triglyceride 418.37 and 406.21, cholesterol 5.48 and 3.67, albumin 1.02 and 0.35, total protein 1.89 and 4.59, calcium was -3.54 and -1.83 mg/dL; the net difference in breast milk volume in the intervention group compared to the control group increased, which was not statistically significant but was significant in terms of value. No significant difference was observed in other components of breast milk. Conclusion In this single-center study, foot reflexology massage showed a trend towards increasing the volume of breast milk, total protein and calcium, although it was not statistically significant. Therefore, it needs further investigation. Trial registration IRCT, IRCT20221220056872N1. Registered 22 January 2023- prospective registered, https://irct.behdasht.gov.ir/trial/67512 .